2009
DOI: 10.1051/dst/2009022
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of processed cheese against hyperlipidemia in rats

Abstract: -The purpose of this study was to examine the effects of intake of processed cheeses containing different types of fats on plasma lipid profile and lipid peroxidation using hypercholesterolemic rats as an experimental model. This study included three types of processed cheeses: the first two contained vegetable oils and the third contained milk fat only. Five groups of rats (8 animals each) were fed balanced diet (normal), hypercholesterolemic diet (control), and hypercholesterolemic diet containing one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Dairy products are complex foods that contain fat, calcium, magnesium, potassium, vitamin D, certain amino acids and other lipid micro-constituents which may contribute to the prevention of hypertension, atherosclerosis, type 2 diabetes mellitus (T2DM) and CVDs (Chrysant and Chrysant 2013). Data derived from other studies are in good agreement with our work suggesting that fat derived from cheese could reduce CVD risk markers in rats (Abd El-Salam and Mohamed 2009). Additionally, studies have been found to underline the antihypertensive (Ramchandran et al 2011) and cholesterol-lowering effect (Ataie-Jafari et al 2009;Hjerpsted et al 2011) of dairy products in hypercholesterolaemic subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Dairy products are complex foods that contain fat, calcium, magnesium, potassium, vitamin D, certain amino acids and other lipid micro-constituents which may contribute to the prevention of hypertension, atherosclerosis, type 2 diabetes mellitus (T2DM) and CVDs (Chrysant and Chrysant 2013). Data derived from other studies are in good agreement with our work suggesting that fat derived from cheese could reduce CVD risk markers in rats (Abd El-Salam and Mohamed 2009). Additionally, studies have been found to underline the antihypertensive (Ramchandran et al 2011) and cholesterol-lowering effect (Ataie-Jafari et al 2009;Hjerpsted et al 2011) of dairy products in hypercholesterolaemic subjects.…”
Section: Discussionsupporting
confidence: 86%
“…These finding were consistent with those of previous studies (Biong et al , 2004, Davis et al , 1993, Hjerpsted et al , 2011). It was assumed that the high calcium content in the cheese-based diet could promote the excretion of fat as calcium soaps, therefore reducing fat adsorption and increasing fecal fat excretion (Nakajima et al , 1992, El-Salam and Mohamad, 2009). In addition, it was suggested that the presence of casein and whey protein in cheese are other factors that result in the hypocholesterolemic effect of cheese consumption.…”
Section: Discussionmentioning
confidence: 99%
“…EI-Salam and Mohamed (2009) studied the effect of processed cheese on plasma lipid profile and lipid peroxidation and found that it could significantly reduce the lipid peroxidation. There is evidence to suggest that two bioactive tripeptides, valyl-prolyl-proline (VPP) and isoleucyl-prolyl-proline (IPP), found in cheese (Bütikofer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%